POPULATION FLUCTUATION AND BAIT ASSESSMENT FOR THE CAPTURE OF Rhynchophorus palmarum L. (COLEOPTERA: CURCULIONIDAE) IN AFRICAN PALM - POSADA-F., FRANCISCO J.; AARON-D., ENRIQUE (Revista Colombiana de Entomología, 1991)
The palm weevil, Rhynchophorus palmarum L., has become a serious economic pest of the oil palm because it acts as a vector of the nematode Rhadlnaphelenchus cocophilus (Cobb), which causes the red-ring disease, prevalent in around 100 ha in the plantations of the departments of Magdalena and Cesar. The most efficient methodology to reduce the disease is the use of insect traps. In this connection, an experiment was carried out in order to determine the population fluctuation, the efficiency of different baits, and its cost. The study was performed at Sevilla, in Cienaga (Magdalena, Colombia), located at 20 m.a.s.1., with an average temperature of 27’C, and relative humidity of 76%. The population fluctuation was evaluated using a jar type trap with molasses, water, sugar cane (1, 2,5, and 1 pound, respectively) plus 2,5 ml of methomylThe traps were revised every week in order to register captures and the bait was changed every month. The baits evaluation was done during tour months using a completely randomized design with four replicates, including as treatments panela (unrefined brown sugar) and molasses, with four different replacement frequencies: 8, 15,21 and 30 days, During the study, the palm weevil was captured with an average of 12,5 per trap, recording the highest population in March 1989; with a female: male ratio of 1,03;1,0. There were no differences between the evaluated baits, but from the economic point of view the panela was the cheapest. The highest captures were obtained when the bait was changed every 21 to 30 days.